Rzeczowniki z sufiksem -iwo w gwarach Małopolski południowej .......... 409 - Kucharzyk, Renata (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
NOUNS WITH THE -IWO SUFFIX IN THE DIALECTS OF SOUTHERN LESSER POLAND The article is devoted to nouns with the -iwo suffix occurring in the dialects of southern Lesser Poland. The analysis aims to illustrate the specific functioning of this suffix in dialects, as compared to standard Polish. The research material is sourced from the card index of Słownik gwar polskich [‘Dictionary of Polish dialects’] of the Polish Academy of Sciences (PAN), and from recently published dialectal dictionaries and dialectological studies from the area of southern Lesser Poland. The analysis utlizes both elements of synchronic description, and a diachronic approach.